Analisis Viktimologi terhadap Remaja Korban Bullying di Lingkungan Sekolah - Rafly Alikhsan; Amanda Claudy Amore (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
This study aims to analyze the victimological aspects of adolescents who are victims of bullying in the school environment. Bullying remains a significant social issue that negatively affects the psychological, social, and academic development of adolescents. This research employs a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation involving adolescents who have experienced bullying. The data were analyzed through data reduction, data display, and conclusion drawing.The results indicate that victims of bullying tend to have certain characteristics such as low self-confidence, introverted behavior, and limited social interaction skills. The forms of bullying identified include verbal bullying, social bullying, and cyberbullying. The impacts experienced by victims include psychological distress such as anxiety and low self-esteem, difficulties in social interaction, and decreased academic performance. From a victimological perspective, both individual and environmental factors play a significant role in the occurrence of victimization. Therefore, active involvement from schools, families, and communities is necessary to prevent and address bullying in order to create a safe environment for adolescents.